Effect of Anti-TNF-α on the Development of Offspring and Pregnancy Loss During Pregnancy in Rats - Er, Ayse; Aydin, Ibrahim; Dik, Burak (Acta Scientiae Veterinariae, 2016)
Background: Etanercept binds soluble tumor necrosis factor-alpha (TNF-α) and is classified as pregnancy risk category B. Increase in TNF-α level causes preterm labour or miscarriage. Lipopolysaccharides trigger preterm birth and abortion via producing of pro-inflammatory cytokines. Cytokines are divided into two groups as pro-inflammatory and anti-inflammatory. TNF-α is a pro-inflammatory cytokine, whereas interleukin (IL)-10 is an anti-inflammatory cytokine. IL-10 predominant in normal pregnancy while TNF-α characterize in abortion and recurrent abortion. The aim of this study was to determine the effect of etanercept on the development of offspring and lipopolysaccharide-induced pregnancy loss. Materials, Methods & Results: Twenty-eight female and 7 male Wistar rats (5-6 months old) were used in this study. The rats were fed a standard pelleted diet and tap water ad libitum. After female rats were caged with males for 1 day, the presence of a vaginal plug was designated as day 0 of pregnancy. Twenty-eight pregnant Wistar rats were divided into 4 equal groups, as follows: control (0.3 mL of Normal Saline Solution intravenously on day 10 of pregnancy); etanercept (0.8 mg kg-1/day intraperitoneally on days 9 and 10 of pregnancy); lipopolysaccharide (160 µg kg-1 intravenously on day 10 of pregnancy); and etanercept + lipopolysaccharide. Blood samples were obtained from the tail vein on day 10 of pregnancy (3 h after lipopolysaccharide administration). All animals were followed during pregnancy. Pregnancy rates and offspring characteristics were determined. TNF-α and IL-10 levels were measured using an ELISA reader. Etanercept alone did not have any negative effects, and etanercept did not prevent (P < 0.05) lipopolysaccharide-induced pregnancy loss. Higher TNF-α and IL-10 levels were measured (P < 0.05) in the etanercept + lipopolysaccharide group compared to other groups. Discussion: It is well known that use of etanercept does not increase pregnacy loss. In this study, higher pregnancy rates were determined in the control and etanercept groups than the lipopolysaccharide and etanercept + lipopolysaccharide groups. The proportion of fetal deaths in lipopolysaccharide administered pregnant subjects was decreased by the use of anti-TNF-α agents. While the concentrations of TNF-α are low in the onset of pregnancy period, the concentrations of TNF-α increases a peak level during the onset of labour. Embryonic resorption is affected by Th1 cytokines (TNF-α and lL-2) and low-dose lipopolysaccharide without any affecting mother survival, and in the early pregnancy term, the implantation area of embryo is enormously sensitive to these molecules. In the current study, etanercept increased the concentration of TNF-α and the concentration of IL-10 when compared to the lipopolysaccharide group. IL-10 has a protective role, while TNF-α is an abortive factor during pregnancy. Thus, etanercept did not prevent pregnancy loss. This finding may have reflected an insufficient dose of etanercept. Adverse effects did not occur in the offspring of the etanercept or control groups, and there was no difference between the two groups statistically. Adverse pregnancy outcomes such as stillbirth, low birth weight, spontaneous abortion and herediter malformations are not associated with TNF-α inhibitors. In conclusion, etanercept does not pose a major teratogenic risk and has no preventive effects with respect to infection-dependent pregnancy loss.